A plague of sorcerers - Zambreno, Mary Frances, 1954- (New York : Hyperion Paperbacks for Children, 1996)
When a magic plague begins to take its toll of the wizards in the Empire, Jermyn, a newly-apprenticed wizard, and Delia, his skunk familiar, must find a way to stop it.
Sequel: Journeyman wizard.
Notable/Best Books (A.L.A.).
School Library Journal.
Wilson's Junior High School.
7.5.
7.5
Keywords: Magic -- Fiction; Wizards -- Fiction; Magic -- Fiction; Wizards -- Fiction